Comparison of the effectiveness and safety of perampanel and oxcarbazepine as monotherapy in children and adolescents with newly diagnosed focal epilepsy - Yi, Jia-Qin; Huang, Sheng; Wu, Miao-Juan; Ma, Jie-Hui; Huang, Li-Juan; Liang, Song; Sun, Dan (Frontiers in Pharmacology, 2023)
Objective: To compare the effectiveness and safety of perampanel and oxcarbazepine as monotherapy in children with focal epilepsy (FE). Methods: This is an ambispective, single center, non-inferiority study comparing the effectiveness and safety of perampanel (PER) monotherapy and oxcarbazepine (OXC) monotherapy in children with newly diagnosed FE. The primary endpoint was 6-month seizure freedom rate. The secondary endpoints included retention rate, responder rate, and seizure freedom rate at 3, 6 and 12 months. Adverse events (AEs) were also recorded for both groups. Results: One hundred and thirty children and adolescents aged from 4 to 18 years old newly diagnosed with FE between May 2020 to November 2022 in Wuhan Children’s Hospital were included. There were 71 patients in PER group and 59 patients in OXC group. In per protocol set (PPS), 50 (78.1%) in the PER group and 43(78.2%) in the OXC group completed 6 months treatment without seizures. The lower 95% CI (66.0%-87.5%) limit of PER was higher than the non-inferiority margin of 62.4% (80% of the 6-month seizure freedom rate in OXC group), PER was noninferior to OXC. The 3-month and 12-month seizure freedom rate was 77.1% and 82.9% for PER, while it was 80.4% and 75.8% for OXC. There were no serious adverse events in both groups. Conclusion: PER showed comparable effectiveness and safety compared with OXC in children with newly diagnosed focal epilepsy, which might be an effective and safe treatment for in children and adolescents with newly diagnosed FE.